Analisa Kinerja Mesin Freezer Kapasitas 100 Liter dengan Penambahan Subcooler untuk Proses Pembekuan Es Batu - Anwar, Mochamad; Sudrajat, Danu; Belyamin; Wibowo, Berbudi; Soeboer, Deni Achmad; Moryanto, Sri (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2026)
The independent demand for ice by coastal communities and small-scale business operators is commonly fulfilled using small-scale freezer units. The cooling prici performance is a critical parameter for evaluating operational effectiveness and energy efficiency. This study evaluates the performance of a 100-liter freezer equipped with a subcooler compared to a standard configuration. The system was tested for 240 minutes at an ambient temperature of approximately 30 °C, with thermal and electrical parameters recorded every 20 minutes. Temperature, operating pressure, and power consumption data were analyzed to determine thermodynamic parameters, including the actual coefficient of performance (COP), Carnot COP, and system efficiency. The results indicate that the freezer configuration with a subcooler produces a lower refrigerant temperature after the compressor, ranging from 62–63 °C, compared to 71–72 °C in the standard configuration. The refrigerant temperature after the condenser decreased from 46–47 °C to 32–33 °C. The discharge pressure was reduced from 90–95 psi in the standard system to 60–80 psi in the subcooled system. The actual COP increased from 1.93–2.95 to 2.26–3.44, while the Carnot COP increased from 2.82–3.97 to 3.08–4.36. System efficiency was higher in the freezer with the subcooler, ranging from 73–79%, compared to 68–74% in the standard freezer. Overall, the integration of a subcooler improves heat transfer performance, reduces compressor workload, and increases energy efficiency by approximately 3–6%.